Lost in transduction: Critical considerations when using viral vectors - Hines, William C.; Hines, William C. (Frontiers in Cell and Developmental Biology, 2023)
The application of retroviral vectors in the laboratory requires considerations that often go overlooked but are often easy to circumvent. Here, we discuss the relationship between the observed transduction efficiency of a cell population and per-cell viral insertions—and describe how differential cell-type susceptibilities can confound results. We consider the math underlying this problem and review an alternative approach to the commonly used ‘multiplicity of infection' (MOI) method of titering and using viral vectors in the biomedical research laboratory.